2013
DOI: 10.1007/s12522-013-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic adhesiolysis for patients with Asherman's syndrome: menstrual and fertility outcomes

Abstract: Purpose Most patients with Asherman's syndrome present with infertility and menstrual problems. In this retrospective clinical study, we analyzed patients with Asherman's syndrome who underwent hysteroscopic adhesiolysis to examine their associated symptoms, disease etiologies, and fertility outcomes. Methods Twenty‐seven patients with Asherman's syndrome that were diagnosed using hysteroscopy were recruited. The chief complaints were infertility, hypomenorrhea, and amenorrhea. Each case of Asherman's syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
2
26
2
Order By: Relevance
“…Characteristics of the included studies are given ( Table 1 ). In our systematic review the classification systems used included ( Table 2 ) those from the American Fertility Society [ 9 , 16 , 27 , 28 , 34 – 36 , 41 , 44 , 45 ], European Society of Gynaecological Endoscopy [ 7 , 29 , 39 ], American Society for Reproductive Medicine [ 11 ], European Society of Hysteroscopy [ 29 , 38 ], European Society of Human Reproduction and Embryology [ 45 ], modified Sugimoto criteria [ 13 ], and the March classification system [ 18 ]. Three studies [ 7 , 29 , 45 ] reported the stages of adhesion using 2 classification systems; however, several studies [ 8 , 12 , 19 , 30 – 33 , 37 , 42 , 43 ] did not provide any information of the classification system used.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies are given ( Table 1 ). In our systematic review the classification systems used included ( Table 2 ) those from the American Fertility Society [ 9 , 16 , 27 , 28 , 34 – 36 , 41 , 44 , 45 ], European Society of Gynaecological Endoscopy [ 7 , 29 , 39 ], American Society for Reproductive Medicine [ 11 ], European Society of Hysteroscopy [ 29 , 38 ], European Society of Human Reproduction and Embryology [ 45 ], modified Sugimoto criteria [ 13 ], and the March classification system [ 18 ]. Three studies [ 7 , 29 , 45 ] reported the stages of adhesion using 2 classification systems; however, several studies [ 8 , 12 , 19 , 30 – 33 , 37 , 42 , 43 ] did not provide any information of the classification system used.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have evaluated the outcome after hysteroscopic adhesiolysis. Overall restoration of normal menstruation is observed in 75%–100% 4,38,50,55,56. The effect on fertility is influenced by several other factors, eg, the age of the patient, and whether infertility is primary or secondary.…”
Section: Management Of Asmentioning
confidence: 99%
“…In the literature, the incidence of perforation without ultrasonography reached 9% in severe cases of Asherman's syndrome [24]. It was therefore advised to use ultrasonography to safeguard against perforation of the uterus [25].…”
Section: Discussionmentioning
confidence: 99%